An economy of industries and its aggregate representation - D’ADDA, C. (PSL Quarterly Review, 2013)
Commonly, macroeconomic texts seek to represent the functioning of the economy by the fiction of the one good system. Keynes’ General Theory of Employment, Interest and Money was, in fact, far more complex. Keynes theorised in an economy made up of industries in the Marshallian tradition. The author examines Keynesian assumptions that we may consider to be unrealistic, such as making employment homogeneous and his adoption of the Marshallian framework. This paper interprets Chapter 3 of the General Theory which, in the author's view, does no more than explore the limitations of Marshall in practice. JEL: E12, B13, B22